A Re-examination of Verb Agreement with Conjoined Subjects in Biblical Hebrew - Scheumann, Jesse R. (Journal for semitics, 2021)
Partial agreement refers to sentences that have conjoined subjects but a singular verb. Although word order is commonly cited in the Biblical Hebrew literature as affecting partial agreement, there is no consensus regarding such an effect. This syntactic study of all clauses with a compound subject in Genesis-2 Kings reveals that a singular verb always agrees with the initial conjunct. The results are incorporated in a cross-linguistic typology of partial agreement. Other key results are that only a coordinate compound headed by an R-expression (rather than a pronoun) is a subject, and that partial agreement is the dominant pattern when the verb and first conjunct are contiguous. A two-step process of Agree—first in syntax and then in phonology—is able to produce the optional partial agreement patterns, laying a better foundation for future studies to analyse the semantic and discourse-analysis effects on verb agreement.